Livelihood, Ability to Pay, and the Original Meaning of the Excessive Fines Clause - McLean, Nicholas M. (2013)
This article highlights the circuit split that has recently emerged regarding the Eighth Amendment's Excessive Fines Clause in the years since United States v. Bajakajian. The article introduces the traditional English legal principle of salvo contenemento and examines the role this principle played in informing the meaning of the excessive fines under English law. It then goes on to consider American colonial understandings of salvo contenemento, undertaking a brief survey of post-Founding considerations of the meaning of the phrase excessive fines. The article studies the public meaning of the Excessive Fines Clause at the time of the Fourteenth Amendment's ratification then examines the modern case for fully reintegrating the economic survival norm of salvo contenemento into Eighth Amendment jurisprudence